Non-Isothermal Kinetic Methods: Workbook and Laboratory Manual - Igor V. Arhangel`skii (Textbooks 1: Max Planck Research Library for the History and Development of Knowledge, 2013)
In the modern world of ever-advancing technologies, actual tests of products and processes are more and more often preceded, if not replaced, by computer modeling. This saves the time and resources required for actual tests, and enables a better understanding of processes that occur in the course of tests. Preliminary computer modeling favors prudent planning of experiments. Calculations in thermal analysis are used everywhere, for example, in estimating the efficiency of thermal insulation of pipelines and in estimating the critical overheating conditions for some chemical substances under which their decomposition, self-heating, explosion, and so forth, occurs. This methodical manual focuses on a small aspect of calculations in thermal analysis dealing with constructing kinetic models from thermogravimetry and differential scanning calorimetry experimental data.